Implementasi Metode RAD pada Sistem Pengaduan Masyarakat (SIPMAS) di Desa Logung Menggunakan Framework Laravel - susanto, susanto; pramono, basworo ardi; Widyandayani, Anita Galih; Patmawati, Putri (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Community complaints about village government are still manual in nature, namely that the community has to report to the RT first, then the RT reports to village officials verbally, making work inefficient. With the development of increasingly sophisticated technology, public complaints can be made using the public complaints system (SIPMAS). The use of a public complaints system makes the complaint process more practical, easier, and faster. In creating a community complaints system in Logung Village, was built using the Laravel framework. The system development methods used are Rapid Application Development (RAD) and Unified Modeling Language (UML) for diagram design. It is hoped that the aim of creating this program is to help village officials manage complaint data online.